Implications of grotesque features of scientific creations in Margaret Atwood’s selected speculative fiction - Ong, Li Yuan (2019)
Speculative fiction is a type of literary fictions, which consists of future speculations of the socio-political issues and set in a believable alternate setting. These speculations consist of exaggerating and hyperbolic features and patterns that induce fear, and uncertainties, and nauseating situation to the readers. Margaret Atwood’s MaddAddam trilogy is such example, which portrays grotesque posthuman future, as the human survivors are no longer amazed by the scientific inventions. As they are no longer relying on the scientific inventions, they realise they have unknowingly accepted some of the inventions as normalcy or social norms. Atwood has cleverly demonstrated these conditions through a few examples of genetically modified animals and modern medications, which raised a sense of discomfort and uncanny among the characters. The study intends to examine the grotesque nature of the genetically modified animals and modern medications in Margaret Atwood’s MaddAddam trilogy, via the conceptual framework of the grotesque proposed by Justin D. Edwards and Rune Graulund. In this study, the analysis employs two concepts, which are the concepts of the uncanny and monstrosity to study MaddAddam trilogy, especially Oryx and Crake, The Year of the Flood and MaddAddam. These three texts are analysed in order to highlight the grotesque features of the scientific creations and the characters’ responses towards these creations. The analysis and discussion show that there is a number of physical features and functions that cause the characters to feel fearful and repulsed of them in Atwood’s MaddAddam trilogy. Based on the conceptual framework of the grotesque, the concepts of the uncanny and monstrosity show the physicality of the scientific creations, which formed exaggeration, gruesome and monstrous features. As a result, this causes the characters and readers to experience disorientation towards the grotesque nature of the scientific creations due to the unfamiliar state of savagery in their social norms. The monstrosity of the creations is portrayed based on the violation of traditional binary oppositions, such as familiar and unfamiliar, human and non-human, culture and savagery as well as attraction and repulsion. In conclusion, this study can increase the significance of the study by noting the grotesque realism of physical body and the acceptance of the grotesque realities of man’s imperfect material life due to the awareness of the impossibility of awareness.